When Cape Slavery Ended: Evidence from a New Slave Emancipation Dataset - Kate Ekama; Johan Fourie; Hans Hesse; Lisa Martin (African Economic History Network (AEHN), 2020)
The emancipation of the enslaved across the British Empire in 1834 is one of the major events in world history. Slave-owners received cash compensation for freeing the enslaved. In the Cape Colony, appraisers assigned a value to the former slaves which was later used to calculate the compensation. We transcribed 37,412 valuation records and matched them to compensation claims to compile a novel emancipation dataset. Our analysis of these individual-level records gives us a new picture of the enslaved population in the Cape at the time of the emancipation. We highlight the nature and distribution of the Cape valuations, noting differences between districts in the enslaved and slave-owner populations. This new dataset not only allows us to ask new questions about an understudied period in South African history, but can illuminate broader discussions about the impact of slavery on economic development, in South Africa and beyond
Keywords: N27; N37; 330; slave valuation; emancipation; compensation; British Empire; Cape Colony